Interface Oral Health Science 2014 2015
DOI: 10.1007/978-4-431-55192-8_26
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Liposome-Encapsulated Nisin in the Prevention of Dental Caries

Abstract: Dental caries is a common oral bacterial infectious disease. Its prevention requires the control of the causative pathogens, such as Streptococcus mutans, that exist within dental plaque. Nisin is a proteinaceous bacteriocin produced by Lactococcus lactis that is used to suppress bacterial infections. It has an inhibitory mode of action on a wide range of gram-positive bacteria. Improvements in the medical benefits of antibacterial agents can be achieved if they can be retained in liposomes for a long period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…2002; Tsumori et al . 2015). Liposomes that can adhere to the dental surface may prevent caries by sustained release of antimicrobial agents (Yamakami et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2002; Tsumori et al . 2015). Liposomes that can adhere to the dental surface may prevent caries by sustained release of antimicrobial agents (Yamakami et al .…”
Section: Resultsmentioning
confidence: 99%
“…Liposomal systems have been widely used to encapsulate many different substances. Liposomes can retain and control the release of sensitive molecules at a moderate rate and have the potential to improve their therapeutic effects (Trif et al 2001;Benech et al 2002;Tsumori et al 2015). Liposomes that can adhere to the dental surface may prevent caries by sustained release of antimicrobial agents (Yamakami et al 2013).…”
Section: Anti-biofilm Characteristicmentioning
confidence: 99%
“…Nano-sized liposomes—called nano-liposomes—are promising vehicles for the encapsulation and delivery of different bioactive compounds such as enzymes, vitamins, and food additives, as well as the delivery of therapeutic bacteriocins to target cells [ 16 ]. Liposome encapsulation protects bacteriocins ( Figure 2 ) from degradation caused by physicochemical environment or protease action [ 45 ], susceptibility to which is a major limitation of bacteriocins. Various studies addressing the protection of bacteriocins from protease degradation have been reported [ 46 , 47 ].…”
Section: Bacteriocin–nanomaterials Combinationmentioning
confidence: 99%
“…Malheiros et al [ 85 ] showed excellent stability and antibacterial activity of liposome-encapsulated bacteriocins against the growth of L. monocytogenes . Prevention of dental caries is also possible using liposome-encapsulated nisin [ 45 ]. Similarly, García-Toledo et al [ 86 ] investigated the anti-listerial activity of pediocin encapsulated with liposome with excellent synergistic activity.…”
Section: Applicationsmentioning
confidence: 99%
“…Drug delivery by liposomes with different encapsulated bioactive molecules (such as bacteriocins, enzymes, antiseptics, antibiotics, and vegetal compounds) can assure a controlled delivery of some antimicrobial substances at infection's situs, with a great efficiency in dental caries and every other biofilm-associated infection [152]. Encapsulation technologies, which may shield substances such as nisin from degradation by digestive enzymes and effectively deliver the encapsulated contents at the same time, represent new direction in the field of preventive medicine [153].…”
Section: Altered Gene Expression Represents Another Difference Betweementioning
confidence: 99%